2017
DOI: 10.1111/ejss.12407
|View full text |Cite
|
Sign up to set email alerts
|

Reducing conditions in soil of Gallocanta Lake, northeast Spain

Abstract: Saline wetlands have received limited attention from researchers and this neglect has often resulted in their degradation and limited conservation, and insufficient information to design conservation and management plans. Gallocanta Lake is a nature reserve of international importance for winter birds. The importance of the soil here, which supports niches and protected habitats for certain species of birds, has been recognized more recently. The soil of Gallocanta Lake undergoes strong oscillations of saturat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…Furthermore, site C, which is closer to the centre of the lake, had a higher conductivity compared to A and B (45 ± 4 mS/cm). Chlorine and bicarbonate concentrations were not measured in this study but concentrations reported previously, considering cross-shore variations, reached up to 1890 and 14 mM, respectively 23 , 30 .
Figure 1 Study site.
…”
Section: Saline Endorheic Gallocanta Lakecontrasting
confidence: 74%
See 1 more Smart Citation
“…Furthermore, site C, which is closer to the centre of the lake, had a higher conductivity compared to A and B (45 ± 4 mS/cm). Chlorine and bicarbonate concentrations were not measured in this study but concentrations reported previously, considering cross-shore variations, reached up to 1890 and 14 mM, respectively 23 , 30 .
Figure 1 Study site.
…”
Section: Saline Endorheic Gallocanta Lakecontrasting
confidence: 74%
“…S6 ). Dissolved sulphide and iron sulphides such as framboidal pyrite, which can form in sediments containing ferrous iron and sulphide 26 , have been previously detected in Gallocanta Lake 25 , 26 , 30 . Also, in site B purple bacteria were observed in the water overlying the sediment cores immediately after collection, suggesting further sulphide oxidation on the water–sediment interface (Fig.…”
Section: Sulphur Cycling Processes In a Sulphate Rich Systemmentioning
confidence: 98%
“…events (Tian et al, 2017), the P released into the surface water of Gallocanta Lake may accumulate in the soil at the lake edge, especially under anaerobic conditions (Castañeda et al, 2017), as probably occurs at GA19 (7.4 mg kg -1 , Table 2).…”
Section: Version Postprintmentioning
confidence: 99%
“…The Indicator of Reduction in Soils (IRIS) is one of three U.S.‐approved techniques (NRCS, 2015) used to demonstrate soils are reducing (Berkowitz & Sallee, 2011; Castañeda, Luna, & Rabenhorst, 2017; Hodges, King, Pett‐Ridge, & Thompson, 2018). Iron‐oxide IRIS rely on iron reduction (Jenkinson & Franzmeier, 2006; Castenson & Rabenhorst, 2006).…”
Section: Introductionmentioning
confidence: 99%